2022
DOI: 10.33462/jotaf.1059728
|View full text |Cite
|
Sign up to set email alerts
|

Kilis Keçilerinin Yetiştirici Koşullarındaki Laktasyon Süt Verimi ve Süt Kalite Özellikleri Üzerine Bir Araştırma

Abstract: Bu çalışma, Kilis keçilerinde laktasyon süt verimi ve süt kalite özellikleri arası ilişkileri belirlemek amacıyla yapılmıştır. Süt verimi ve laktasyon süresinin saptanmasında Kilis merkezde bulunan iki farklı işletmeden toplam 170 baş Kilis keçisi deneme materyali olarak kullanılmıştır. Kilis keçilerinde laktasyon süt verimi ve süresine ilişkin tanımlayıcı değerler; 201.05±6.75 kg ve 225.22±7.75 gün olarak bulunmuştur. Çalışma materyali keçilerde, süt kalite özellikleri olarak değerlendirilen toplam kuru madde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The findings suggest that the live weights of Kilis goats during the postpartum and mating periods were within the range of 36.0 kg to 58.0 kg previously reported for various goat genotypes aged 2-5 years in different regions (Erduran, 2017;Ünalan and Ceyhan, 2017;Daşkıran and Yılmaz, 2018;Özdemir and Keskin, 2018). This situation can be explained by the variability of goats depending on their genetic capacity, social rank, area conditions, feeding, care, yield direction and grazing capacity of the pasture (Ocak, 2016;Castillo-Zuñiga et al, 2022;Erduran, 2023a The growth and development potential of goats can last up to 5 ages.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The findings suggest that the live weights of Kilis goats during the postpartum and mating periods were within the range of 36.0 kg to 58.0 kg previously reported for various goat genotypes aged 2-5 years in different regions (Erduran, 2017;Ünalan and Ceyhan, 2017;Daşkıran and Yılmaz, 2018;Özdemir and Keskin, 2018). This situation can be explained by the variability of goats depending on their genetic capacity, social rank, area conditions, feeding, care, yield direction and grazing capacity of the pasture (Ocak, 2016;Castillo-Zuñiga et al, 2022;Erduran, 2023a The growth and development potential of goats can last up to 5 ages.…”
Section: Resultssupporting
confidence: 82%
“…However, milk and fertility yields are not at the desired level in the pasturebased breeding system (Çelik and Olfaz, 2015;Atay and Gokdal, 2016;Erduran, 2021). Kilis goat is an indigenous goat breed adapted to warm climatic conditions that is known for its fertility and milk yield in the southeast of Türkiye, generally in Kilis, Gaziantep, Hatay, and Şanlıurfa provinces (Daşkıran and Yılmaz, 2018;Özdemir and Keskin, 2018). Interest in dairy goat breeding is increasing day by day in parallel with the increase in demand for processing goat milk and dairy products in the Central Anatolia Region (Erduran, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This study examined the impacts of several mycorrhiza species on organic carrot farming and revealed that antioxidant activity was positively impacted. (Kiracı et al 2014). In one study, it was determined that the biological control agents used in tomatoes did not have a signi cant effect on total phenolic matter or antioxidant activity, and there were changes depending on the application (Boyno et al 2022).…”
Section: Effects Branched Broomrape Contamination and Biological Cont...mentioning
confidence: 99%